Phoenix math for the 21st century learners : 9 - Puro, Lucy M.; Reyes, Victor O.; Sy Tan, Josephine L.; Cenita, Ruben B.; Gadia, Clemente (Quezon City : Phoenix Publishing House, Inc., 2019)
"Phoenix Math for the 21st Century Learners is a series of textbooks for high school students. It is designed to address the students' different learning capabilities. The series is based on the K to 12 Curriculum Minimum Learning Competencies of the Department of Education (DepEd). It aims to help students learn to think mathematically and to help them see how mathematics works in a modern society. Each section is usually introduced through the use of inductive reasoning, taht is, students are provided with several examples so that they can make propositions out of the illustrations given".
English text.
Keywords: Mathematics -- Study and Teaching